Melestarikan hubungan flora dan manusia melalui pemakanan ulam: kajian terhadap masyarakat Utara Semenanjung. - Ratna Roshida Ab Razak (Environmental Management Society, Malaysia, 2011)
The preservation of food heritage and the Malay community's nutrition has been substantial especially in the world where it is well regarded as borderless. In the era where the eating culture has adopted a more universal approach , with specific regards to various foreign influences that can pose a threat to the tastebuds and the normative attributes of eating, traditional foods naturalness must be sustained, so that it will not be impacted by the passing of time , as the saying goes, tak lekang dek panas,tak reput dek hujan, The Emergence of fast food restaurant which mushroom, also not fogetting the international status restaurants, can be seen as an extraordinary and an interesting globalised phenomenon.Although this is seen as unique and a good tranformation, some adverse effects may be brought about especially when the culture of the eating habit of the locals is noted to lean more towards food that is more instant and when traditional foods are no longer seen as appealing, let alone to be placed on ahigh position in the society. The change of lifestyle has also altered the eating trend of the Malaysians towards Something with "better class". Traditional food have been given the backseat. The natural greens as an example, which is the type of food that had never left the tables of the traditional community homes, has started to be abandoned when the salad was introduced more widely in the market. Such a phenomenon can gradually erode the position of the local community,s traditional eating habit and at this juncture, automatically an asset of the Malay culture, which is eating will have been affected. Therefore, this paper will attempt to delve into the world of ulam in the context of the Malay societys nutrition in the northern region.